Proceedings of the first International Conference on Animal Production and Environment (Agricultural Publishing House,Đại học Cần Thơ, 2012)
Session 1: Animal Nutrition, Feed Technology and Environment, Session 2: Biotechnology in Animal Science, Session 3: Animal Healthcare and Environment, Session 4: Animal Production in response to green-house gas emission, Session 5: Animal Food Products: Processing technology and food safety